2017
DOI: 10.2147/ijn.s133832
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of drug nanocarriers

Abstract: Pharmaceutical design has enabled important advances in the prevention, treatment, and diagnosis of diseases. The use of nanotechnology to optimize the delivery of drugs and diagnostic molecules is increasingly receiving attention due to the enhanced efficiency provided by these systems. Understanding the structures of nanocarriers is crucial in elucidating their physical and chemical properties, which greatly influence their behavior in the body at both the molecular and systemic levels. This review was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(44 citation statements)
references
References 103 publications
0
39
0
Order By: Relevance
“…Based on diameter, small (<50 nm), large (50-500 nm) and giant (>500 nm) liposomes can be distinguished (Banerjee, 2001;Morton et al, 2012). Alternatively, a classification can be made on the basis of whether a liposome possesses uni-, oligo-, or multi-lamellar bilayers (Morton et al, 2012;Manaia et al, 2017). Liposomes can consist of naturallyoccurring lipids or synthetically-made lipids (sometimes called "artificial" liposomes).…”
Section: Summary Of Different Types Of Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on diameter, small (<50 nm), large (50-500 nm) and giant (>500 nm) liposomes can be distinguished (Banerjee, 2001;Morton et al, 2012). Alternatively, a classification can be made on the basis of whether a liposome possesses uni-, oligo-, or multi-lamellar bilayers (Morton et al, 2012;Manaia et al, 2017). Liposomes can consist of naturallyoccurring lipids or synthetically-made lipids (sometimes called "artificial" liposomes).…”
Section: Summary Of Different Types Of Liposomesmentioning
confidence: 99%
“…Within the range of DOPA concentrations applied, zeta potentials remained below the critical limit of FIGURE 4 | Zeta potentials of liposomes. Liposome suspensions are considered to be unstable when their zeta potential is between −30 and +30 mV (Manaia et al, 2017). Zeta potentials between −10 and +10 mV are considered to represent uncharged liposomes.…”
Section: Cationic Liposomesmentioning
confidence: 99%
“…This behavior increases their solubility in the medium and decreases their surface-to-volume ratio. Liposomes can be prepared through reverse-phase evaporation, the injection of phospholipids dissolved in an organic phase into a drug-containing aqueous phase, detergent dialysis, microfluidic hydrodynamic focus, supercritical reverse-phase evaporation, electroformation, microfluid liposome formation, and thin lipid film formation [126].…”
Section: Polymersomes and Liposomesmentioning
confidence: 99%
“…Representative graphs based on an independent measurement of the zeta potential and particle size distribution are shown in Figure 1a,b. Researchers have shown that TEM imaging is an effective and powerful tool for characterizing the morphology of nano-and micro-structured biomaterials and drug carriers as it uses more powerful beams to produce higher resolution images with more details and information [30,31]. The TEM micrographs showed minimally aggregated, dispersed RDS particles that appeared as darker areas relative to the background, with rounded outer morphologies (Figure 1c,d).…”
Section: Size Polydispersity Index and Zeta Potential Determinationmentioning
confidence: 99%